2018
DOI: 10.18203/2394-6040.ijcmph20182170
|View full text |Cite
|
Sign up to set email alerts
|

School health performance score: a comparative study between rural and urban school performance

Abstract: INTRODUCTIONEducation is a best indicator for lifelong health with improved quality of life. Those with more years of schooling tend to have better health, well-being and healthier behaviors. Education is an important mechanism for enhancing health and well-being of individuals as it reduces the need for health care, associated costs of dependence, lost earnings and human suffering. It also helps promote and sustain healthy lifestyles and positive choices, supporting and nurturing human development, human rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…These results agree with previous studies which indicated that students from rural schools performed better compared with their counterparts from urban schools (Nidup, 2022;Oyeromi, et al, 2018). At the same time, the results contradict other studies which revealed that urban schools performed better than rural schools (Sumida & Kawata, 2021;Vishwajeet & Girish, 2018). This implies that the performance of students in both rural and urban schools may be context specific, likely related to the availability of teaching resources.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results agree with previous studies which indicated that students from rural schools performed better compared with their counterparts from urban schools (Nidup, 2022;Oyeromi, et al, 2018). At the same time, the results contradict other studies which revealed that urban schools performed better than rural schools (Sumida & Kawata, 2021;Vishwajeet & Girish, 2018). This implies that the performance of students in both rural and urban schools may be context specific, likely related to the availability of teaching resources.…”
Section: Discussionsupporting
confidence: 86%
“…Different studies confirm that secondary school students in Africa perform poorly in geography (Anlimachie, 2019;Eze, 2021;Mwesiga, 2017;Opoku, et al, 2020;Yahaya, et al, 2021). By comparing rural and urban schools, some studies found that students from rural schools perform better compared with their counterparts from urban schools (Nidup, 2022;Oyeromi, et al, 2018;) and this contradicted by others revealing that urban schools perform better than rural schools (Opoku-Asare & Siaw, 2015; Sumida & Kawata, 2021;Vishwajeet & Girish, 2018).…”
Section: Performance Of Geography Studentsmentioning
confidence: 98%
“…Good monitoring and evaluation ensures adequate and optimal implementation of school health services (Chidiebere et al, 2016). Scientists from various fields consider the problem of the creation of a safe health education environment for primary schools and monitoring its effectiveness: monitoring the medical (Calmeiro, 2019;Jourdan et al, 2018;Wahl, 2017) and sanitary (Chavan & Chavan, 2018;Madureira et al, 2015) provision of the educational environment; monitoring of school physical activity policies (Jordán, et al, 2017;Kohl et al, 2012;Taylor et al, 2011); remote health monitoring technologies (Toscos, Connelly, & Rogers, 2012) programs to measure the child's holistic development (Seema, 2019); monitoring as a primary information system in education (Lunyachek, 2011) etc.…”
Section: Introductionmentioning
confidence: 99%